Evaluating Constraints to Animal Traction Development and Sustainability in the Upper Noun Valley, North West Region Cameroon - Mboungho, Nuipokoh Oscar; Ibrahim, Manu; Solefack, Dongmo (Asian Journal of Agriculture and Rural Development, 2018)
The principal aim of this study was to find out the reasons for the low adoption of animal traction in the Upper Noun Valley community. The general views were; to find out the level of animal traction adoption, to see its level of profitability, to examine its importance on agricultural sustainability and the overall constraints and benefits involved in animal traction. Combinations of multi-stage random and purposive sampling procedures were applied to obtain the needed information from oxen-farmers and institutions. A cross sectional data was collected and analysed from random sample of 90 oxen farmers within the Upper Noun Valley Community. Data were collected and analysed using Statistical Package for Social Sciences (SPSS) and Microsoft Excel. The study revealed that small-scale farmers encountered several sustainability challenges from inappropriate implements, pasture difficulty, lack of training and repair centres, poor animal housing. Animal traction sustainability depends on its; affordability, flexibility, timeliness on farm and organic manure provision. In order to overcome the alarming food insecurity in Cameroon, both the government and stakeholders should regain consciousness on abandoned training centres, and minimum packages should be given to small-scale farmer as well as local blacksmiths and veterinary centres be provided at the Divisional level.